Airborne pollen grains at Chittagong University Campus, Bangladesh - Pasha, MK; Hossain, Mohammad Sohrab (Bangladesh Journal of Botany, 2010)
A total of 4,549 airborne pollen grains were recorded and classified into 34 pollen morpho-types in an airborne pollen survey at Chittagong University campus, during October, 2006 to September 2007. Maximum contribution was made by Poaceae type (32.89%), followed by Cyperaceae (5.94%), Mesua nagassarium (3.98%), Amaranthaceae (3.72%), Mimosaceae (3.58%), Artocarpus heterophyllus (2.75%), Cocos nucifera (2.73%), Asteraceae (2.95%) and some other types specific to this region. The unidentified pollen contributed to an average of 16.90%. Maximum pollen concentration was observed in the month of March (20.27%) and minimum in July (2.70%). Key words: Airborne; Pollen grains; Palynology; Chittagong Univ. Campus; Bangladesh DOI: 10.3329/bjb.v38i1.5117 Bangladesh J. Bot. 38(1): 39-46, 2009 (June)